Implementasi Metode Servqual Dalam Sistem Informasi Klinik Afrina Dental Care Berbasis Web - Paranindra Ardhana Biroe Aurori; Raissa Amanda Putri (G-Tech: Jurnal Teknologi Terapan, 2024)
Klinik Afrina Dental Care, operating in Simpang Empat District, Asahan Regency since 2006, offers a variety of dental care services. This study aims to improve service quality through the application of the Servqual method in a web-based information system, which measures five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The analysis results indicate that the overall service quality exceeds patient expectations. The "Assurance" dimension recorded the largest gap (10.308), indicating that assurance and trust are highly appreciated by patients. Conversely, "Reliability" showed the smallest gap (5.385), highlighting the need for improvement in reliability. Although the overall service is satisfactory, certain aspects related to reliability require more attention to bridge the gap between expectations and reality.